A high-performance interpenetrating network structure gel powder and its preparation method and application

By ionic cross-linking modification of nanocellulose and preparing gel powder with interpenetrating network structure, the shortcomings of aqueous polyurethane coatings in terms of mechanical properties and thermal stability are solved, and a high-performance polyurethane coating is achieved.

CN119192610BActive Publication Date: 2025-04-08SUZHOU GANGRUITONG NANO MATERIALS TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411699761.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-04-08
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing water-based polyurethane coatings have shortcomings in terms of mechanical properties and thermal stability, and the mechanical properties of nanocellulose are relatively low, making it difficult to effectively improve the performance of the coating.

Method used

By modifying nanocellulose with metal ions as additives, ion-crosslinked nanocellulose hydrogels are prepared, and gel powders with interpenetrating network structure are prepared based on this, and the polyurethane coating is further modified to improve its mechanical properties and corrosion resistance.

Benefits of technology

A stable and dense structure is formed on the surface of the polyurethane coating, which significantly improves the mechanical properties and corrosion resistance of the coating, and makes up for the "soft and weak" defects of nanocellulose gel materials in the mechanical structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192610B_ABST
    Figure CN119192610B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of honeycomb materials, and specifically relates to a high-performance interpenetrating network structure gel powder, a preparation method and application thereof. Metal ions are used as auxiliary agents to modify a nanocellulose solution, and an ion-crosslinked nanocellulose hydrogel is prepared. Then, under stirring conditions, a polyamic acid mixed solution is added dropwise to the nanocellulose hydrogel solution. Under the splitting effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the polyamic acid mixed solution can form a fine liquid flow in the nanocellulose hydrogel solution in a stirring state, and gradually precipitate to form polyamic acid nanofibers, which then form an interpenetrating network structure with nanocellulose after imidization. The gel powder is used to modify polyurethane coatings, and a stable dense structure can be formed on the surface of the polyurethane coating, thereby greatly improving the mechanical properties and anti-corrosion ability of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of honeycomb materials, and in particular relates to a high-performance interpenetrating network structure gel powder and a preparation method and application thereof. Background Art

[0002] Polyurethane (PU), the full name of which is polyurethane, contains a large number of carbamate structures (-NHCOO-) on the main chain, and is usually synthesized by condensation of isocyanate and polyether or diol polyester. There are many different methods for synthesizing polyurethane, synthetic raw materials and reaction conditions, which makes the structure of each polyurethane very different. Precisely because of the diversity of methods for synthesizing polyurethane, it has a variety of structures. For example, polyurethane synthesized using polyester diol as raw material will have ester bonds, and polyester polyurethane has high strength, good flexibility and UV resistance. Therefore, different synthesis methods make polyurethane carry different functional groups, which can meet the requirements of multiple fields and have a wide range of applications. It has been widely used in industrial fields such as films, coatings, fibers, medicines, adhesives and construction.

[0003] Generally speaking, the synthesis of PU coatings is formed by the polymerization reaction of polyisocyanate monomers and polyol monomers under suitable catalysts and additives. At present, PU has been widely used in industries such as construction, footwear, coal, automobiles, coatings, and biomedicine. It is precisely because of the diversity of raw materials for synthetic PU coatings that the structure and performance of the formed PU are diversified, which is one of the reasons why PU coatings have a wide range of applications. Polyurethane coatings can be divided into solvent-based polyurethanes and waterborne polyurethanes (WPU) according to the different dispersion media. WPU, which uses water as a medium and evaporates without solvent, has excellent properties, such as low price, convenient transportation, fast curing speed, good thermal stability, strong adhesion, and high film strength, making it widely used in many fields, such as coatings, adhesives, printing inks and other industrial fields. However, in order to ensure the dispersibility of WPU in water, a large number of hydrophilic groups are introduced during the preparation process, which will greatly reduce the water resistance. In addition, the mechanical properties and thermal stability are still lower than those of solvent-based PU coatings. Therefore, in recent years, in order to improve the performance deficiencies of WPU and its functionalization, the research on WPU modification has gradually increased. Common modification methods include cross-linking modification, copolymerization modification, blending modification and composite modification, which has also greatly promoted the rapid development of waterborne polyurethane.

[0004] Blending modification is to physically blend the prepared WPU emulsion with other types of emulsions or some nanomaterials, and evenly disperse them through mechanical stirring or ultrasonic dispersion, so as to prepare the required functional coating. Nanomaterials refer to materials that have at least one dimension in the nanoscale range in three-dimensional space or are composed of them as basic units. Adding nanoparticles to polymers is one of the important methods to improve the performance of polymer materials. At present, there are many nanomaterials used to enhance and improve waterborne polyurethane, mainly including: nanocellulose, nanometal particles, nanocarbon materials, nanooxides, etc. CN118852963A discloses a heat-reflecting heat-insulating coating, in which nano-titanium dioxide is evenly dispersed in a cellulose aerogel matrix and a polyurethane coating, and the aggregation of nano-titanium dioxide is inhibited. The cellulose aerogel improves the flame retardant properties of the coating. CN117801653A discloses a highly elastic hydrophobic radiation-cured wood lacquer skin-feel coating, and the addition of hyperbranched nanocellulose hydrogel realizes the skin-tactile properties of the coating on the wood surface, and the physical and mechanical properties and durability of the coating are improved by reacting the -NH2 group in the hyperbranched nanocellulose hydrogel and the -NCO group in the radiation light-cured coating. CN110105531A and CN107474680A also disclose adding gel materials to the coating to improve the corresponding properties of the coating. However, the above-mentioned technology is only to add modified cellulose gel. As a natural fiber material, the mechanical properties of cellulose gel are relatively low; and cellulose gel has a large specific surface area. Due to the interaction between molecules and the influence of hydrogen bonds, cellulose gel is easily aggregated, so that its dispersibility and stability in polyurethane coatings are poor. At the same time, since the process of preparing cellulose gel is relatively complicated, the cost is high, and the yield is low, it is not suitable for large-scale industrialization. Summary of the invention

[0005] The purpose of the present invention is to provide a high-performance interpenetrating network structure gel powder and its preparation method and application. The present invention uses metal ions as an auxiliary agent to modify the nanocellulose solution to prepare an ion-crosslinked nanocellulose hydrogel; then, based on the gel, a gel powder with an interpenetrating network structure is prepared, further improving the mechanical properties of the cellulose gel. The gel powder is used to modify the polyurethane coating to form a stable dense structure on the surface of the polyurethane coating, thereby greatly improving the mechanical properties and anti-corrosion ability of the coating.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a high-performance interpenetrating network structure gel powder comprises the following steps:

[0008] (1) treating natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose;

[0009] (2) under stirring conditions, adding a solution containing metal ions to a deionized water dispersion of nanocellulose, and obtaining a nanocellulose hydrogel solution after sol-gelation;

[0010] (3) preparing a polyamic acid solution in an organic solvent using diamine and dianhydride as raw materials, then adding polyvinyl pyrrolidone and stirring to obtain a polyamic acid mixed solution; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is (0.01-0.5):1;

[0011] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization reagent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure;

[0012] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

[0013] Cellulose is a common high molecular polymer in nature, widely found in plants such as cotton, hemp and wood, and has the advantages of good biocompatibility, renewability, biodegradability, environmental friendliness and non-toxicity. Nanocellulose is made from cellulose, and has at least one dimensional space size of less than 100nm. Nanocellulose composite hydrogel materials not only retain the unique physical and chemical properties of cellulose, such as hydrophilicity, biocompatibility, biodegradability, high chemical activity and dimensional stability, but also have new structural characteristics given by micro-nano processing technology, such as light weight, softness, high specific surface area, high crystallinity, high strength, high modulus and mild chemical activity. Because the surface of cellulose nanofibers has abundant hydroxyl groups, cellulose exhibits high hydrophilicity, and can quickly form a uniform and stable nanocellulose suspension in the coating, which is widely used.

[0014] However, nanocellulose has low mechanical properties and has limited performance improvement on the coating. In addition, due to its large specific surface area and strong hydrogen bonding, nanocellulose is prone to agglomeration, and has poor compatibility with the matrix and uneven dispersion. In previous works (CN118667223A, CN118812911A, CN118702962A, etc.), the inventors first prepared hydrogels and then directly added fibrous fillers or water-soluble polyamic acid salts. In this method, the fibrous fillers can only be dispersed outside the hydrogel and cannot penetrate into the gel to form an interpenetrating structure. The water-soluble polyamic acid salts cannot be precipitated into fibrous structures.

[0015] In order to solve the problems existing in nanocellulose, the present invention first prepares nanocellulose gel, and then prepares polymer nanofibers through a precipitation process. The precipitation method is a common process for preparing polymer nanofibers in the prior art, but directly pouring polyamic acid into the precipitation liquid will obtain micron or even millimeter-sized fibers, and nanometer-sized fiber structures cannot be prepared.

[0016] The present invention drips the polyamic acid mixed solution into the nanocellulose hydrogel solution under stirring. Among them, the nanocellulose not only plays a role in forming an interpenetrating network structure; more importantly, under the state of rapid stirring, the nanocellulose fibers in the solution can play a "sickle"-like splitting role, so that the polyamic acid mixed solution is split into bundles with smaller diameters, thereby reducing the diameter of the polyamic acid fibers. In order to further make the fiber diameter reach the nanometer level, and also to enable the polyamic acid solution to form a stable bundle structure in the rapidly stirred nanocellulose hydrogel solution, the generation of the nanofiber structure is promoted. The present invention adds a certain amount of polyvinyl pyrrolidone. On the one hand, the polyvinyl pyrrolidone molecule contains a pyridine ring structure, which can form a hydrogen bond with the imine structure and carboxyl group on the polyamic acid, provide an adsorption force, and enable the organic solution "bundle" of the polyamic acid to be stably dispersed in the nanocellulose hydrogel solution; on the other hand, the polyvinyl pyrrolidone also has a hydrophilic effect, and can hydrate with the water molecules in the nanocellulose hydrogel solution. When the polyamic acid mixed solution is added dropwise to the nanocellulose hydrogel solution, the adsorption force and hydration force of polyvinyl pyrrolidone cause polyvinyl pyrrolidone to be dispersed in the outer surface of the "tow" of the organic solution of polyamic acid. Since polyvinyl pyrrolidone itself has a high viscosity, it can promote the stability of the "tow" structure. Under the shear force provided by stirring and the "cutting" effect of nanocellulose, the "tow" can gradually become longer and thinner, thereby increasing the aspect ratio of the polyimide fiber and promoting the formation of the nanofiber structure. The molecular weight of polyvinyl pyrrolidone is not particularly limited, and its specific number average molecular weight can be 8000-200000.

[0017] In previous work, the inventor used a steam bath method to prepare nanocellulose hydrogel. Although this method is relatively simple, the steam bath can only contact the solution at the gas-liquid interface, the gel reaction is insufficient, the uniformity is poor, and the gelation process is slow, which is difficult to promote and use on a large scale. In order to solve this problem, the present invention uses an ion crosslinking process to prepare nanocellulose hydrogel. Ionic crosslinking is a non-covalent crosslinking bond formed by the combination of metal ions and ligands on nanocellulose. In this ion-crosslinked nanocellulose gel, the crosslinked network ensures the macroscopic appearance of the gel, and dissipates energy by destroying the gel when it is subjected to external force, thereby improving the mechanical properties of the gel. Moreover, the nanocellulose gel prepared by ion crosslinking has certain reversible properties: in the process of dripping the polyamic acid mixed solution, it is inevitable that the nanocellulose gel structure will be destroyed. After the nanocellulose hydrogel prepared by the steam bath method is destroyed, the structure is irreversible. After the nanocellulose gel prepared by ion crosslinking is destroyed by mechanical force, ion crosslinking will occur again in the subsequent static process, giving the hydrogel reversible properties. Furthermore, the nanocellulose hydrogel prepared by ionic crosslinking can crosslink with the subsequently formed polyimide nanofibers through the electrostatic effect of ions, thereby increasing the binding force between the nanocellulose and polyimide nanofibers and making the formed interpenetrating network structure more stable. Moreover, after the introduction of metal ions into the hydrogel network to form an ionic crosslinking network, the gel's ability to dissipate energy when subjected to external forces is improved, thereby increasing the mechanical properties of the gel.

[0018] In general, ionic crosslinking can improve the stability of the gel structure matrix. During the stirring process, under the breaking effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the polyamic acid mixed solution can form fine liquid flows in the stirred nanocellulose hydrogel solution and gradually precipitate to form polyamic acid nanofibers, thereby forming an interpenetrating network structure with nanocellulose.

[0019] This composite functional gel material not only retains the original properties of the gel material, but also combines the high modulus, high strength, thermal stability, high chemical activity and other properties of nanocellulose and polyimide nanofibers with the solution properties of hydrogels, making up for the "soft and weak" defects of nanocellulose gel materials in mechanical structure, and laying the foundation for potential application development of gels.

[0020] Furthermore, in step (1), the natural cellulose raw material is at least one of cotton, bamboo powder, waste paper, flax, sisal, straw, and bagasse; the treatment method includes at least one of high-pressure homogenization, acid hydrolysis, enzymatic hydrolysis, and TEMPO oxidation; the diameter of the nanocellulose is 10-100nm and the length is 5-20μm. Furthermore, the nanocellulose of the present invention is prepared by TEMPO oxidation. The full name of TEMPO is 2,2,6,6-tetramethylpiperidinyl oxide, which is an organic nitrogen oxide with weak oxidizing properties. This method has a short reaction time, is non-toxic, and has a low cost, and the morphology and size of the prepared nanocellulose are relatively uniform. By controlling the process parameters of the TEMPO oxidation method, the aspect ratio of the nanocellulose can be effectively adjusted and the degree of interaction between the nanocellulose and the polyimide nanofiber can be improved.

[0021] Furthermore, in step (2), the metal ion is Li + 、Na + , K + , Ca 2+ Mg 2+ 、Zn 2+ , Cu 2+ 、Al 3+ At least one of .

[0022] Furthermore, in step (2), the source of metal ions is at least one of chloride, sulfate, carbonate or nitrate corresponding to the metal.

[0023] Furthermore, in step (2), the mass ratio of the metal ions to the nanocellulose is (0.01-0.1):1.

[0024] Furthermore, in step (3), the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is (0.5-2):1; further, the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is (1-1.5):1. The types of diamine and dianhydride are not particularly limited, and the molar ratio of dianhydride monomer to diamine monomer is 1:(0.95-1.05); the organic solvent used in the reaction is at least one of N-methylpyrrolidone, dimethylformamide, and dimethylacetamide. Specifically, the dianhydride monomer is at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride, hexafluoro dianhydride, and 3,3',4,4'-benzophenone tetracarboxylic dianhydride; the diamine monomer is at least one of 4, 4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, and p-phenylenediamine.

[0025] Furthermore, in step (4), the stirring rate is 400-900 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of (1-3):1, and the mass of the mixture is 10-30% of the mass of the polyamic acid solution. Furthermore, in step (4), the stirring rate is 600-700 rpm. An appropriate stirring rate can avoid the reduction of the aspect ratio of the polyimide nanofibers due to too fast stirring rate, and can also prevent the defect of a thicker diameter due to too slow stirring rate.

[0026] On the other hand, the present invention also provides an application of the high-performance interpenetrating network structure gel powder, and the high-performance interpenetrating network structure gel powder is used in the field of polyurethane coatings.

[0027] The polyurethane coating comprises the following components in parts by weight: 100 parts of aqueous polyurethane dispersion; and 0.5-5 parts of the gel powder having an interpenetrating network structure.

[0028] The large number of hydroxyl groups on the surface of nanocellulose in the gel powder will form hydrogen bonds with the polyurethane matrix molecules, enhancing the interfacial interaction between the gel powder and the polyurethane matrix, solving the technical problem of poor compatibility between polyimide nanofibers and polyurethane coatings. Polyimide nanofibers have high mechanical properties, solving the "soft and weak" defect of nanocellulose gel materials in mechanical structure. Nanocellulose and polyimide nanofibers form an interpenetrating structure, allowing the two to be fully entangled, exerting a synergistic reinforcement effect, and improving the density and mechanical properties of the polyurethane coating.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The production process of the present invention is simple, easy to operate, highly efficient, and industrially scalable.

[0031] (2) Nanocellulose hydrogel was prepared by ionic crosslinking. The crosslinked network ensures the macroscopic appearance of the gel and dissipates energy by breaking the gel when subjected to external force, thereby improving the mechanical properties of the gel. In addition, the nanocellulose gel prepared by ionic crosslinking has certain reversible properties and can be crosslinked with the subsequently formed polyimide nanofibers through the electrostatic effect of ions, thereby improving the bonding force between nanocellulose and polyimide nanofibers and making the formed interpenetrating network structure more stable.

[0032] (3) First, prepare nanocellulose hydrogel and construct nanocellulose-based gel material, and then add the polyamic acid mixed solution to the nanocellulose hydrogel solution under stirring. Under the splitting effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the polyamic acid mixed solution can form fine liquid flows in the stirred nanocellulose hydrogel solution and gradually precipitate to form polyamic acid nanofibers, thereby forming an interpenetrating network structure with nanocellulose.

[0033] (4) Hydrogen bonds will occur between the nanocellulose in the gel powder and the polyurethane matrix molecules, solving the technical problem of poor compatibility between polyimide nanofibers and polyurethane coatings. Polyimide nanofibers solve the "soft and weak" defect of nanocellulose gel materials in mechanical structure. Nanocellulose and polyimide nanofibers form an interpenetrating structure, and the two play a synergistic role in improving the density and mechanical properties of the polyurethane coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a scanning electron microscope image of the gel powder prepared in Example 10;

[0035] Figure 2 This is a scanning electron microscope image of the gel powder prepared in Comparative Example 1. DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to the present application. Among them, the specific preparation process of nanocellulose in the following examples and comparative examples is as follows: (1) Removal of wax from bamboo powder: Add bamboo powder to a mixed solution composed of toluene and ethanol (volume ratio 3:1), mechanically stir for 24 hours, wash and dry, and set aside; (2) Removal of lignin from bamboo powder: Add the product of step (1) to a three-necked flask, then add 2wt% sodium chlorite solution, adjust the pH to 4, and react at 80°C for 6h, wash and dry, and set aside; (3) Removal of hemicellulose from bamboo powder: Add the product of step (2) to a 5wt% potassium hydroxide solution, stir at 90°C for 3h, wash and dry, and set aside; (4) Formation of nanocellulose: disperse bamboo cellulose powder in a mixed solution of TEMPO, sodium bromide and distilled water, slowly add sodium hypochlorite into the solution, stir evenly, adjust the pH to 10 and react for 4 hours, centrifuge and wash to obtain TEMPO-treated cellulose; the mass ratio of bamboo cellulose powder, TEMPO, sodium bromide and sodium hypochlorite is 1:0.02:0.1:2; place the TEMPO-treated cellulose in an ultrasonic cell crusher for 30 minutes, and freeze-dry to obtain nanocellulose with a diameter of 80 nm and a length of 10 μm.

[0037] Example 1

[0038] A method for preparing a high-performance interpenetrating network structure gel powder comprises the following steps:

[0039] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0040] (2) Under stirring conditions, a solution containing metal ions is added dropwise to the deionized water dispersion of nanocellulose to obtain a nanocellulose hydrogel solution after sol-gelation; the metal ions are Ca derived from calcium chloride. 2+ ; The mass ratio of metal ions to nanocellulose is 0.04:1;

[0041] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.03:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1:1; the molar ratio of dianhydride monomer to diamine monomer is 1:0.96; the organic solvent used in the reaction is N-methylpyrrolidone; the dianhydride monomer is 3,3',4,4'-biphenyltetracarboxylic dianhydride; and the diamine monomer is 4,4'-diaminodiphenylmethane;

[0042] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 400 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 1:1, and the mass of the mixture is 18% of the mass of the polyamic acid solution;

[0043] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

[0044] A polyurethane coating comprises the following components in parts by weight:

[0045] 100 parts of waterborne polyurethane dispersion; 4 parts of high-performance interpenetrating network structure gel powder.

[0046] Example 2

[0047] A method for preparing a high-performance interpenetrating network structure gel powder comprises the following steps:

[0048] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0049] (2) Under stirring conditions, a solution containing metal ions is added dropwise to the deionized water dispersion of nanocellulose to obtain a nanocellulose hydrogel solution after sol-gelation; the metal ions are Al derived from aluminum chloride. 3+ ; The mass ratio of metal ions to nanocellulose is 0.07:1;

[0050] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.5:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.5:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.03; the organic solvent used in the reaction is dimethylformamide; the dianhydride monomer is pyromellitic dianhydride; and the diamine monomer is a mixture of 4, 4'-diaminodiphenyl ether and 4,4'-diaminodiphenylmethane in a molar ratio of 1:1;

[0051] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 900 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 3:1, and the mass of the mixture is 30% of the mass of the polyamic acid solution;

[0052] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

[0053] A polyurethane coating comprises the following components in parts by weight:

[0054] 100 parts of waterborne polyurethane dispersion; 4 parts of high-performance interpenetrating network structure gel powder.

[0055] Example 3

[0056] A method for preparing a high-performance interpenetrating network structure gel powder comprises the following steps:

[0057] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0058] (2) Under stirring conditions, a solution containing metal ions is added dropwise to the deionized water dispersion of nanocellulose to obtain a nanocellulose hydrogel solution after sol-gelation; the metal ions are Ca derived from calcium chloride. 2+ ; The mass ratio of metal ions to nanocellulose is 0.04:1;

[0059] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.45:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.03; the organic solvent used in the reaction is dimethylacetamide; the dianhydride monomer is a mixture of pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride in a molar ratio of 1:1; the diamine monomer is 4, 4'-diaminodiphenyl ether;

[0060] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 500 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 3:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0061] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

[0062] A polyurethane coating comprises the following components in parts by weight:

[0063] 100 parts of waterborne polyurethane dispersion; 4 parts of high-performance interpenetrating network structure gel powder.

[0064] Example 4

[0065] A method for preparing a high-performance interpenetrating network structure gel powder comprises the following steps:

[0066] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0067] (2) Under stirring conditions, a solution containing metal ions is added dropwise to the deionized water dispersion of nanocellulose to obtain a nanocellulose hydrogel solution after sol-gelation; the metal ions are Al derived from aluminum chloride. 3+ ; The mass ratio of metal ions to nanocellulose is 0.05:1;

[0068] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.08:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.1:1; the molar ratio of dianhydride monomer to diamine monomer is 1:0.98; the organic solvent used in the reaction is dimethylformamide; the dianhydride monomer is 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride; the diamine monomer is a mixture of 4, 4'-diaminodiphenyl ether and p-phenylenediamine in a molar ratio of 3:1;

[0069] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 500 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 1.2:1, and the mass of the mixture is 16% of the mass of the polyamic acid solution;

[0070] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

[0071] A polyurethane coating comprises the following components in parts by weight:

[0072] 100 parts of waterborne polyurethane dispersion; 4 parts of high-performance interpenetrating network structure gel powder.

[0073] Example 5

[0074] A method for preparing a high-performance interpenetrating network structure gel powder comprises the following steps:

[0075] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0076] (2) Under stirring conditions, a solution containing metal ions is added dropwise to the deionized water dispersion of nanocellulose to obtain a nanocellulose hydrogel solution after sol-gelation; the metal ions are Ca derived from calcium chloride. 2+ ; The mass ratio of metal ions to nanocellulose is 0.06:1;

[0077] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.3:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.3:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.04; the organic solvent used in the reaction is a mixture of N-methylpyrrolidone and dimethylacetamide in a volume ratio of 1:1; the dianhydride monomer is a mixture of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 3,3',4,4'-benzophenonetetracarboxylic dianhydride in a molar ratio of 2:1; the diamine monomer is 4, 4'-diaminodiphenyl ether;

[0078] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 800 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2.5:1, and the mass of the mixture is 24% of the mass of the polyamic acid solution;

[0079] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

[0080] A polyurethane coating comprises the following components in parts by weight:

[0081] 100 parts of waterborne polyurethane dispersion; 4 parts of high-performance interpenetrating network structure gel powder.

[0082] Example 6

[0083] A method for preparing a high-performance interpenetrating network structure gel powder comprises the following steps:

[0084] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0085] (2) Under stirring conditions, a solution containing metal ions is added dropwise to the deionized water dispersion of nanocellulose to obtain a nanocellulose hydrogel solution after sol-gelation; the metal ions are Ca derived from calcium chloride. 2+ ; The mass ratio of metal ions to nanocellulose is 0.01:1;

[0086] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.2:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.3:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is N-methylpyrrolidone; the dianhydride monomer is a mixture of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 3,3',4,4'-diphenylethertetracarboxylic dianhydride in a molar ratio of 2:1; the diamine monomer is 4, 4'-diaminodiphenyl ether;

[0087] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 600 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0088] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

[0089] A polyurethane coating comprises the following components in parts by weight:

[0090] 100 parts of waterborne polyurethane dispersion; 4 parts of high-performance interpenetrating network structure gel powder.

[0091] Example 7

[0092] A method for preparing a high-performance interpenetrating network structure gel powder comprises the following steps:

[0093] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0094] (2) Under stirring conditions, a solution containing metal ions is added dropwise to the deionized water dispersion of nanocellulose to obtain a nanocellulose hydrogel solution after sol-gelation; the metal ions are Ca derived from calcium chloride. 2+ ; The mass ratio of metal ions to nanocellulose is 0.1:1;

[0095] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.2:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.3:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is N-methylpyrrolidone; the dianhydride monomer is a mixture of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 3,3',4,4'-diphenylethertetracarboxylic dianhydride in a molar ratio of 2:1; the diamine monomer is 4, 4'-diaminodiphenyl ether;

[0096] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 600 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0097] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

[0098] A polyurethane coating comprises the following components in parts by weight:

[0099] 100 parts of waterborne polyurethane dispersion; 4 parts of high-performance interpenetrating network structure gel powder.

[0100] Example 8

[0101] A method for preparing a high-performance interpenetrating network structure gel powder comprises the following steps:

[0102] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0103] (2) Under stirring conditions, a solution containing metal ions is added dropwise to the deionized water dispersion of nanocellulose to obtain a nanocellulose hydrogel solution after sol-gelation; the metal ions are Ca derived from calcium chloride. 2+ ; The mass ratio of metal ions to nanocellulose is 0.05:1;

[0104] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.2:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 0.5:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is N-methylpyrrolidone; the dianhydride monomer is a mixture of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 3,3',4,4'-diphenylethertetracarboxylic dianhydride in a molar ratio of 2:1; the diamine monomer is 4, 4'-diaminodiphenyl ether;

[0105] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 600 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0106] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

[0107] A polyurethane coating comprises the following components in parts by weight:

[0108] 100 parts of waterborne polyurethane dispersion; 4 parts of high-performance interpenetrating network structure gel powder.

[0109] Example 9

[0110] A method for preparing a high-performance interpenetrating network structure gel powder comprises the following steps:

[0111] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0112] (2) Under stirring conditions, a solution containing metal ions is added dropwise to the deionized water dispersion of nanocellulose to obtain a nanocellulose hydrogel solution after sol-gelation; the metal ions are Ca derived from calcium chloride. 2+ ; The mass ratio of metal ions to nanocellulose is 0.05:1;

[0113] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.2:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 2:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is N-methylpyrrolidone; the dianhydride monomer is a mixture of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 3,3',4,4'-diphenylethertetracarboxylic dianhydride in a molar ratio of 2:1; the diamine monomer is 4, 4'-diaminodiphenyl ether;

[0114] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 600 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0115] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

[0116] A polyurethane coating comprises the following components in parts by weight:

[0117] 100 parts of waterborne polyurethane dispersion; 4 parts of high-performance interpenetrating network structure gel powder.

[0118] Example 10

[0119] A method for preparing a high-performance interpenetrating network structure gel powder comprises the following steps:

[0120] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0121] (2) Under stirring conditions, a solution containing metal ions is added dropwise to the deionized water dispersion of nanocellulose to obtain a nanocellulose hydrogel solution after sol-gelation; the metal ions are Ca derived from calcium chloride. 2+ ; The mass ratio of metal ions to nanocellulose is 0.05:1;

[0122] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.2:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.3:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is N-methylpyrrolidone; the dianhydride monomer is a mixture of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 3,3',4,4'-diphenylethertetracarboxylic dianhydride in a molar ratio of 2:1; the diamine monomer is 4, 4'-diaminodiphenyl ether;

[0123] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 600 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0124] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

[0125] A polyurethane coating comprises the following components in parts by weight:

[0126] 100 parts of waterborne polyurethane dispersion; 4 parts of high-performance interpenetrating network structure gel powder.

[0127] Comparative Example 1

[0128] A method for preparing a high-performance interpenetrating network structure gel powder comprises the following steps:

[0129] (1) Processing natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm;

[0130] (2) Under stirring conditions, a solution containing metal ions is added dropwise to the deionized water dispersion of nanocellulose to obtain a nanocellulose hydrogel solution after sol-gelation; the metal ions are Ca derived from calcium chloride. 2+ ; The mass ratio of metal ions to nanocellulose is 0.05:1;

[0131] (3) A polyamic acid solution is prepared in an organic solvent using diamine and dianhydride as raw materials, and then polyvinyl pyrrolidone is added and stirred to obtain a polyamic acid mixed solution; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 1:1; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.3:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is N-methylpyrrolidone; the dianhydride monomer is a mixture of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 3,3',4,4'-diphenylethertetracarboxylic dianhydride in a molar ratio of 2:1; the diamine monomer is 4, 4'-diaminodiphenyl ether;

[0132] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 600 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0133] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

[0134] A polyurethane coating comprises the following components in parts by weight:

[0135] 100 parts of waterborne polyurethane dispersion; 4 parts of high-performance interpenetrating network structure gel powder.

[0136] Comparative Example 2

[0137] A method for preparing a high-performance interpenetrating network structure gel powder comprises the following steps:

[0138] (1) The natural cellulose raw material is treated, and then nanocellulose and polyvinyl pyrrolidone are mixed and stirred evenly to prepare a deionized water dispersion of nanocellulose; the nanocellulose is prepared from bamboo powder by TEMPO oxidation method; the diameter of the nanocellulose is 80 nm and the length is 10 μm; the number average molecular weight of polyvinyl pyrrolidone is 30,000; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is 0.2:1;

[0139] (2) Under stirring conditions, a solution containing metal ions is added dropwise to the deionized water dispersion of nanocellulose to obtain a nanocellulose hydrogel solution after sol-gelation; the metal ions are Ca derived from calcium chloride. 2+ ; The mass ratio of metal ions to nanocellulose is 0.05:1;

[0140] (3) A polyamic acid mixed solution is prepared in an organic solvent using diamine and dianhydride as raw materials; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is 1.3:1; the molar ratio of dianhydride monomer to diamine monomer is 1:1.01; the organic solvent used in the reaction is N-methylpyrrolidone; the dianhydride monomer is a mixture of 3,3',4,4'-biphenyltetracarboxylic dianhydride and 3,3',4,4'-diphenylethertetracarboxylic dianhydride in a molar ratio of 2:1; the diamine monomer is 4,4'-diaminodiphenyl ether;

[0141] (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization agent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the stirring rate is 600 rpm; the chemical imidization agent is a mixture of acetic anhydride and pyridine in a molar ratio of 2:1, and the mass of the mixture is 20% of the mass of the polyamic acid solution;

[0142] (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

[0143] A polyurethane coating comprises the following components in parts by weight:

[0144] 100 parts of waterborne polyurethane dispersion; 4 parts of high-performance interpenetrating network structure gel powder.

[0145] Performance test: The polyurethane coatings prepared in Examples 1-10 and Comparative Examples 1-2 were subjected to hardness test (GB / T6739-2006), paint film adhesion test (GB / T 5210-2006) and salt spray resistance test (GB / T1771-2007); the test results are shown in Table 1.

[0146]

[0147] Figure 1 and Figure 2 The following are scanning electron microscope images of the gel powder prepared in Example 10 and Comparative Example 1. Figure 1It can be seen that the rough-surfaced polyimide nanofibers and nanocellulose form a dense mesh structure that is intertwined with each other, and the interpenetrating network structure is more regular; this indicates that the nanocellulose gel prepared by ionic crosslinking not only improves the stability of the nanocellulose gel matrix, but can also be crosslinked with the subsequently formed polyimide nanofibers through the electrostatic action of ions, thereby increasing the binding force between nanocellulose and polyimide nanofibers, and making the formed interpenetrating network structure more stable. It can be seen that under the splitting effect of nanocellulose and the auxiliary effect of polyvinyl pyrrolidone, the polyamic acid mixed solution can form fine liquid flows in the stirred nanocellulose hydrogel solution, and gradually precipitate out to form polyamic acid nanofibers, which then form an interpenetrating network structure with nanocellulose after imidization. Figure 2 It can be seen that the polyimide nanofiber prepared in Comparative Example 1 presents a thick rod-shaped fiber structure, and nanocellulose is basically not seen in the figure, indicating that due to the large viscosity of polyvinyl pyrrolidone, when its dosage is too much, the droplets added can not be effectively cut, and can only be gradually thinned by the shear force of stirring. At the same time, due to its large viscosity, the nanocellulose gel inside which is difficult to enter can only be attached to the nanocellulose gel network surface in large quantities, and an interpenetrating network structure cannot be formed. Comparative Example 2 adds polyvinyl pyrrolidone to the nanocellulose aqueous dispersion in advance. Due to the presence of abundant hydroxyl groups on the surface of nanocellulose, a strong hydrogen bond can be formed with polyvinyl pyrrolidone, and it is impossible to attach to the polyamic acid surface added subsequently, and the organic solution "tow" of polyamic acid cannot be stably dispersed in the nanocellulose hydrogel solution, affecting the formation of polymer nanofibers.

[0148] The embodiments described in the present invention are merely descriptions of the preferred implementation modes of the present invention, and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should fall within the protection scope of the present invention. The technical contents for which protection is sought in the present invention have all been recorded in the claims.

Claims

1. A method for preparing a high-performance interpenetrating network structure gel powder, characterized in that: The following steps are involved: (1) treating natural cellulose raw materials to prepare a deionized water dispersion of nanocellulose; (2) under stirring conditions, adding a solution containing metal ions to a deionized water dispersion of nanocellulose, and obtaining a nanocellulose hydrogel solution after sol-gelation; (3) preparing a polyamic acid solution in an organic solvent using diamine and dianhydride as raw materials, then adding polyvinyl pyrrolidone and stirring to obtain a polyamic acid mixed solution; the total weight mass ratio of polyvinyl pyrrolidone to diamine and dianhydride raw materials is (0.01-0.5):1; (4) under stirring conditions, adding the polyamic acid mixed solution dropwise to the nanocellulose hydrogel solution; after the addition is completed, adding a chemical imidization reagent; after standing, exchanging with deionized water solvent to obtain a hydrogel with an interpenetrating network structure; the total weight mass ratio of nanocellulose to diamine and dianhydride raw materials is (0.5-2):1; (5) The hydrogel with an interpenetrating network structure is freeze-dried and crushed to obtain a high-performance interpenetrating network structure gel powder.

2. The method for preparing a high-performance interpenetrating network structure gel powder according to claim 1, characterized in that: In step (1), the natural cellulose raw material is at least one of cotton, bamboo powder, waste paper, flax, sisal, straw, and bagasse; the treatment method includes at least one of high-pressure homogenization, acid hydrolysis, enzymatic hydrolysis, and TEMPO oxidation; the nanocellulose has a diameter of 10-100 nm and a length of 5-20 μm.

3. The method for preparing a high-performance interpenetrating network structure gel powder according to claim 1, characterized in that: The metal ion in step (2) is Li + 、Na + , K + , Ca 2+ Mg 2+ 、Zn 2+ , Cu 2+ 、Al 3+ At least one of .

4. The method for preparing a high-performance interpenetrating network structure gel powder according to claim 1, characterized in that: The source of the metal ions in step (2) is at least one of chloride, sulfate, carbonate or nitrate corresponding to the metal.

5. The method for preparing a high-performance interpenetrating network structure gel powder according to claim 1, characterized in that: The mass ratio of the metal ions to the nanocellulose in step (2) is (0.01-0.1):

1.

6. The method for preparing a high-performance interpenetrating network structure gel powder according to claim 1, characterized in that: In step (4), the stirring rate is 400-900 rpm; the chemical imidization reagent is a mixture of acetic anhydride and pyridine in a molar ratio of (1-3):1, and the mass of the mixture is 10-30% of the mass of the polyamic acid solution.

7. A high-performance interpenetrating network structure gel powder, characterized in that: The high-performance interpenetrating network structure gel powder is prepared by the preparation method of any one of claims 1 to 6.

8. An application of a high-performance interpenetrating network structure gel powder as claimed in claim 7, characterized in that: High-performance interpenetrating network structure gel powder is used in the field of polyurethane coatings.

9. A polyurethane coating, characterized in that: Contains the following components in parts by weight: 100 parts of aqueous polyurethane dispersion; 0.5-5 parts of the high-performance interpenetrating network structure gel powder according to claim 7.

Citation Information

Patent Citations

  • Environment-friendly antibacterial waterborne wood coating

    CN107474680A

  • Preparation method of antibacterial coating used for paper

    CN110105531A

  • Preparation method of high-elastic hydrophobic radiation curing wood paint skin feeling coating

    CN117801653A

  • Modified aerogel powder as well as preparation method and application thereof

    CN118667223A

  • Polyimide graphene gel powder as well as preparation method and application thereof

    CN118702962A